PENGARUH MARKET VALUE, VARIANCE RETURN, DAN VOLUME PERDAGANGAN TERHADAP PERIODE KEPEMILIKAN SAHAM (HOLDING PERIOD) - Bintang Lakitang Lubis; Ahmad Rifai; M. Iqbal Harori (Jurnal Perspektif Bisnis, 2020)
The purpose of this study is to determine the effect of market value, variance return and trading volume on the holding period. The sampling technique in this study used a purposive sampling method and obtained as many as 6 companies listed in the IDXBUMN20 index. The data analysis technique used multiple regression panel data models and using the analysis tool Eviews 9. Based on the t test (partial) shows that the market value, variance return and trading volume has significantly effect and negative relationship on holding period in a partial way. Based on the F test (simultaneous) shows that the market value, variance return and trading volume have significantly effect on the holding period.